The value of human epididymis 4, D‐dimer, and fibrinogen compared with CA 125 alone in triaging women presenting with pelvic masses: a retrospective cohort study. (2nd April 2021) - McKendry, Kate; Duff, Stephen; Huang, Yanmei; Redha, Mostafa; Scanlon, Áine; Abu Saadeh, Feras; Gleeson, Noreen; O'Leary, John; Norris, Lucy; O'Toole, Sharon
Abstract: Introduction: CA 125, the biomarker in common clinical use for ovarian cancer, is limited by low sensitivity for early disease and high false positives. The aim of this study was to evaluate several candidate biomarkers, alone or in combination, compared with CA 125 in the prediction of malignant/borderline vs benign tumor status in premenopausal and postmenopausal women with pelvic masses. Material and methods: This was a retrospective observational cohort study set in St James's Hospital, a tertiary referral center for gynecological malignancy in Dublin, Ireland. Women undergoing surgery for pelvic masses between 2012 and 2018 were included. Preoperative human epididymis protein 4 (HE4), the Risk of Ovarian Malignancy Algorithm, the Risk of Malignancy Index I and II, D‐dimer, and fibrinogen were assessed. Logistic regression models were fitted for each biomarker alone and in combination. Receiver operating characteristics‐area under the curve (ROC‐AUC) and partial AUCs in the 90%‐100% specificity range were determined. Results: In all, 89 premenopausal and 185 postmenopausal women were included. In premenopausal women, no biomarker(s) outperformed CA 125 (AUC 0.73; 95% CI 0.63–0.84). In postmenopausal women, HE4 had a partial AUC (pAUC) of 0.71 (95% CI 0.64–0.79) compared with 0.57 (95% CI 0.51–0.69) for CA 125 ( p = 0.009). HE4 + D‐dimer had an improved pAUC of 0.74 (95% CI 0.68–0.81, p < 0.001) and HE4 + D‐dimer + fibrinogen had a pAUC of 0.75 (95% CI 0.68–0.82). Conclusions: A novel biomarker panel of HE4 ± D‐dimer ± fibrinogen outperformed CA 125 alone as a high‐specificity biomarker in postmenopausal women and could aid in the preoperative triaging of pelvic masses. No biomarker(s) outperformed CA 125 in premenopausal women.